Financial risk management in hedging currency exposure - Tserashenkau, Maksim (My University, 2010)
In this research paper, on the contrary, I tried to present the benefits of financial management using derivates for the purpose they were originally invented. Furthermore, the idea for the case study originated from the book “Company Valuation - Value, Structure, Risk” by Marek Capiński and Wiktor Patena. I suppose that the research and case study are topical and also have a substantial value for me from a practical point of view. The following Master thesis consists of 3 main parts. Chapters 1-4 introduce a number of derivative securities, their pricing models and practical implementation for hedging. Some of them are later used in case study. Chapter 5 is dedicated to Value at Risk model, describes its significance to risk analysis and provides some theory on computation. VaR is going to be one of the key parameters for empirical part of the research. The final part – Chapter 6 – is the case study. I will try to use theoretical basis presented in the paper to form possible solutions for risk management on the actual example of a company. The case comprises a single transaction and requires identification of risk sources with further presentation of solutions to hedge risk exposure. Furthermore, attached Excel file contains main calculations together with macro codes designed for the purpose of case study.
Zarządzanie ryzykiem finansowym na przykładzie osłony ryzyka walutowego
Keywords: kontrakty terminowe; opcje; ryzyko; opcje egzotyczne; forward contract; futures contract; options; exotic options; risk